2017
DOI: 10.1161/circresaha.117.310628
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Rigor in Preclinical Cardiovascular Studies

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(83 citation statements)
references
References 74 publications
3
67
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12] It is a veritable plague that undermines the credibility of published studies, hinders clinical translation of basic work, and impedes the progress of medicine. Disquietingly, the problem seems to be getting worse rather than better.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12] It is a veritable plague that undermines the credibility of published studies, hinders clinical translation of basic work, and impedes the progress of medicine. Disquietingly, the problem seems to be getting worse rather than better.…”
mentioning
confidence: 99%
“…It is not the purpose of this editorial to revisit the nature, origins, mechanisms, and consequences of irreproducibility, all of which have been discussed innumerable times in recent years, both in the literature and in ad hoc workshops. [1][2][3][4][5][6][7][8][9][10][11][12] There has been enough discussion; now it is time for action.…”
mentioning
confidence: 99%
“…A recent study published in Circulation Research revealed that a significant lack of methodological rigor (eg, not randomizing participants, blinding analyses, or adequately determining group sizes) is likely at the root of the field's plague of irreproducible data 3. Considering the detrimental effects this has on science and the public's view of scientific research, investigators ardently need to take steps in continuing to discuss and work toward resolving problems of this nature, as was achieved in this session.…”
Section: Scientific Rigor Reproducibility and Transparencymentioning
confidence: 99%
“…5 An interesting question is certainly whether these improvements were because of the journal editorial policy or may even reflect a change in research practice in the basic science stroke community. A post hoc analysis by Ramirez et al 4 came to the conclusion that it is likely a combination of both: Stroke uniquely showed improvements in all study design elements even after adjusting for cardiovascular disorder studied and animal model used, but stroke as the cardiovascular disorder studied was identified as an independent predictor for at least one study design element for every journal examined. 4 Interestingly, but not unexpected, the Ramirez et al 4 report of poor preclinical study quality not to impact on citations at 60 months.…”
Section: See Related Articles P 2341 P 2632mentioning
confidence: 99%
“…A post hoc analysis by Ramirez et al 4 came to the conclusion that it is likely a combination of both: Stroke uniquely showed improvements in all study design elements even after adjusting for cardiovascular disorder studied and animal model used, but stroke as the cardiovascular disorder studied was identified as an independent predictor for at least one study design element for every journal examined. 4 Interestingly, but not unexpected, the Ramirez et al 4 report of poor preclinical study quality not to impact on citations at 60 months. Article citation is a most commonly used measure of research impact but is obviously an imperfect indicator of study quality.…”
Section: See Related Articles P 2341 P 2632mentioning
confidence: 99%